International Competitiveness in Services in Some Middle East and North Africa Countries Using Gravity Model - Al-Majali, Ahmad A.; Adayleh, Radi M. (International Review of Management and Marketing, 2018)
This paper attempts to identify the current state of services competitiveness in some MENA countries, as well as identifying the degree of attractiveness of the region given its general macroeconomic characteristics. The current paper analyzes the changes in the levels of competitiveness of four major service sectors –Transport, Communications, Travel, and Other Business Services- by using the market share position of a number of MENA countries. Gravity model was used by implementing an annual panel data for the identified key variables covering the period 2006-2010. The model displayed in its four equations the existence of gravity between the MENA countries resulting mainly from the low distance between these countries. Oil -exporting countries have a high demand for services exported by oil-importing countries. Also the model illustrates that there is a significant relationship between a country’s GDP, population, distance, and openness, and trade performance indicators such as imports, exports, trade balance, and total trade. In additional to that the competitiveness matrix shows a general improvement in the competitiveness of MENA countries in services trade over the period of the study. Keywords: Gravity model, MENA countries, competitiveness matrix, services competitiveness JEL Classifications: F1, N7